Professional Microsoft SQL Server 2012 reporting services - Turley, Paul (Wrox programmer to programmer, 2012)
A must-have guide for the latest updates to the new release of Reporting ServicesSQL Server Reporting Services allows you to create reports and business intelligence (BI) solutions. With this updated resource, a team of experts shows you how Reporting Services makes reporting faster, easier and more powerful than ever in web, desktop, and portal solutions. New coverage discusses the new reporting tool called Crescent, BI semantic model's impact on report design and creation, semantic model design, and more. You'll explore the major enhancements to Report Builder and benefit from best practices shared by the authors.Builds on the previous edition while also providing coverage of the new features introduced with SQL Server 2012Explains Reporting Services architecture and BI fundamentalsCovers advanced report design and filtering techniques, walking you through each design, discussing its purpose and the conditions where it could be more efficientDiscusses semantic model design, Report Builder, Crescent, and moreTargets business analysts and report designers as well as BI solution developersProfessional Microsoft SQL Server 2012 Reporting Services is mandatory reading if you are eager to start using the newest version of SQL Server Reporting Services.